Lessons from NASA - Williams, Walter C (IEEE spectrum, 1981)
During the Apollo space program, the US National Aeronautics and Space Administration (NASA) prepared its space missions with reliability as the highest goal. Inflation and budget-cutting have changed that policy on some subsequent missions. Nevertheless, reliability remains a high priority, and considerable amounts of project cost are a consequence of building reliability into the NASA systems. Emphasis in providing reliability is centered at the design phase in NASA's work. More component failures have been attributed to errors in design than to any other cause. Thus, NASA's major reliability thrust is in the application of effective design principles and extensive review of designs. When selecting off-the-shelf components, NASA will typically subject the components to burn-in testing to eliminate those units improperly made and subject to early failure. NASA's testing starts at the component level and builds up to testing a complete prototype of the production system.